Badanie etnocentryzmu konsumenckiego Polaków na przykładzie wybranych branż - Miłota, Krzysztof (Research on Ethnocentrism of Polish Customers Using the Example of Chosen Branches, 2006)
The Polish customer does not put his ethnocentrism into action. Many customers declare paying attention to the origin of the product, but research and rising import amounts show that it is only a declaration. This situation is a result of quality matters and knowledge about the real origin of products. Polish customer is pragmatic when shopping and safety, quality, brand, prestige, price, etc. are much more important than origin. The relations between age and ethnocentrism, rising import and declining duties will make ethnocentrism even less important factor in the future. It is very important to use "non-insinuating" techniques when analyzing ethnocentrism: the results are more compact and customers are expected to give their real opinions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (2); 2006; nr 1110, s. 133-154